2003
DOI: 10.1002/jcb.10734
|View full text |Cite
|
Sign up to set email alerts
|

BMP treatment of C3H10T1/2 mesenchymal stem cells induces both chondrogenesis and osteogenesis

Abstract: The molecular mechanisms by which bone morphogenetic proteins (BMPs) promote skeletal cell differentiation were investigated in the murine mesenchymal stem cell line C3H10T1/2. Both BMP-7 and BMP-2 induced C3H10T1/2 cells to undergo a sequential pattern of chondrogenic followed by osteogenic differentiation that was dependent on both the concentration and the continuous presence of BMP in the growth media. Differentiation was determined by the expression of chondrogenesis and osteogenesis associated matrix gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
150
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 44 publications
9
150
0
1
Order By: Relevance
“…The current studies also do not support a positive regulatory role for BMP-4 in osteogenous since: a) as MSC differentiation progresses there is less BMP-4 expressed; b) both Noggin and BMP-2 antagonism lead to increased BMP-4 expression; c) both BMP-2 or BMP-7 induction of osteogenic differentiation leads to down regulation of endogenous BMP-4 expression. Finally, previous data from our laboratory had also shown that C3H10T½ cells in their undifferentiated state expressed high endogenous levels of BMP-4 whereas in a similar fashion as seen in this study, the exogenous addition of BMP-2 and BMP-7 downregualted its expression during skeletal cell differentiation [9].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The current studies also do not support a positive regulatory role for BMP-4 in osteogenous since: a) as MSC differentiation progresses there is less BMP-4 expressed; b) both Noggin and BMP-2 antagonism lead to increased BMP-4 expression; c) both BMP-2 or BMP-7 induction of osteogenic differentiation leads to down regulation of endogenous BMP-4 expression. Finally, previous data from our laboratory had also shown that C3H10T½ cells in their undifferentiated state expressed high endogenous levels of BMP-4 whereas in a similar fashion as seen in this study, the exogenous addition of BMP-2 and BMP-7 downregualted its expression during skeletal cell differentiation [9].…”
Section: Discussionsupporting
confidence: 86%
“…Noggin is naturally expressed during developmental processes and is known to act as non-competitive inhibitor of BMPs 2, 4 and 7 with a low (Kd 1.0×10 −10 ) disassociation constant [20]. Interestingly we were unable to detect BMP-7 in this system, despite being present in control fracture callus tissue specimens at levels equivalent to BMP-2 and 3 in other mesenchymal cell populations [5,9]. Since BMP-7 expression is not detectable, its role in the differentiation of these cultures is considered negligible.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Mid-and late-stage osteogenic markers including OPN, bone sialoprotein (BSP), and OCN are temporal successors to RUNX2 and OSX expression after rhBMP-2 stimulation [63]. The complex temporal expression profiles of OPN, BSP, and OCN have been elucidated [15,16,23,25,26,30,53,59,66]; therefore, a coordinated, temporal RNAi treatment cycle may enhance the duration and intensity of gene silencing and prevent HA deposition in vitro. Consequently, the evolution of RNAi therapeutics must match RNAi targets to their expression profiles.…”
Section: Discussionmentioning
confidence: 99%